Histidine-Tryptophan-Ketoglutarate (HTK) versus Celsior in the Association with Heart Transplant Outcomes. (July 2018) - Ren, Dewei; Estep, Jerry; Graviss, Edward; Nguyen, Duc; Suarez, Eddie; Macgillivray, Thomes; Bruckner, Brian
Abstract : Background: Preservation solution for cardiac donor graft is very important, and affect patient short termor long term survival. Herein, we report our center experience in recienpient outcomes when comparing Histidine-tryptophan-ketoglutarate (HTK) versus Celsior solution. Methods: A total of 223 heart transplants were performed at our institution between January, 2010 and Octber, 2017, encluding 10 heart retransplants. HTK group total is 102, Celsior group total is 121. Demographic, clinical diagnoses, and morbidity were analyzed. Kaplan-Meier statistics was used to calculate and predict survival for 30 days and one years. Multivariate Cox proportional modeling was used to determine the variables associated with mortality in all cohorts. The C statistic was calculated to measure the concordance between model-based risk estimates and mortality. Results: There were 4 patient deaths at one year in HTK group (including 2 deaths in 30 days). There were total 12 deaths at one year in Celsior group (including 10 deaths in 30 days). There was a significant difference in mortality between the two groups at 30 days (P=0.034), but not one year P=0.098). Multivariate Cox proportional modeling yielded several variables, among them: Celsior and BMI>/=35 are the risk factors (p=0.048, P=0.01) at 30 days, BMI>/=35 is the risk factor at one year (P=0.01). Conclusion: The analysis of this cohort showed that HTK solution is better than Celsior solution for cardiac transplant at short-term outcome, BMI >/=35 is the risk factor at short and long term survival. Figure. No caption available.